2012
DOI: 10.1002/term.1478
|View full text |Cite
|
Sign up to set email alerts
|

Stromal vascular fraction isolated from lipo-aspirates using an automated processing system: bench and bed analysis

Abstract: The heterogeneous stromal vascular fraction (SVF), containing adipose‐derived stem/progenitor cells (ASCs), can be easily isolated through enzymatic digestion of aspirated adipose tissue. In clinical settings, however, strict control of technical procedures according to standard operating procedures and validation of cell‐processing conditions are required. Therefore, we evaluated the efficiency and reliability of an automated system for SVF isolation from adipose tissue. SVF cells, freshly isolated using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
70
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(72 citation statements)
references
References 20 publications
(30 reference statements)
2
70
0
Order By: Relevance
“…Similar nonheadto-head data have been published from a different automated system manufactured by Tissue Genesis, Inc. (Honolulu, HI). 29 Flow cytometry data in the publication demonstrate that a substantial fraction of the cells express the CD34 cell surface marker protein indicating that the population isolated contains SVF cells. However, this device is limited to a maximum processing volume of 60 mL of tissue and prepares the cells in a large final volume (35 mL), which required the authors to perform an additional, manual centrifugation step to concentrate the cells before clinical use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar nonheadto-head data have been published from a different automated system manufactured by Tissue Genesis, Inc. (Honolulu, HI). 29 Flow cytometry data in the publication demonstrate that a substantial fraction of the cells express the CD34 cell surface marker protein indicating that the population isolated contains SVF cells. However, this device is limited to a maximum processing volume of 60 mL of tissue and prepares the cells in a large final volume (35 mL), which required the authors to perform an additional, manual centrifugation step to concentrate the cells before clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…12,16 Recently, the United States Government has awarded Cytori Therapeutics, Inc., the developer of the Celution System, with a large research contract for evaluation of the system for potential use in patients with acute radiation exposure with concomitant thermal burn injury. 29 Specifically, the Biomedical Advanced Research and Development Authority (BARDA; a branch of the U.S. Department of Health and Human Services) awarded Cytori a research contract valued at up to US$106 million over 5 years. This contract will support preclinical and clinical research and device development related to use of the Celution System in patients with concomitant thermal burn injury and radiation exposure following a mass casualty event.…”
Section: Discussionmentioning
confidence: 99%
“…This procedure was approved by the University of Michigan Medical School IRB, and conducted based on previously described techniques [10, 11]. Briefly, an Icellator system (Tissue Genesis, Honolulu, HI, USA) and Adipase (Tissue Genesis) were used to gently digest and isolate the SVFCs according to the manufacturers protocols from approximately 60cc of subcutaneous lipoaspirate obtained from a patient undergoing a cosmetic procedure.…”
Section: Methodsmentioning
confidence: 99%
“…The concentration of viable cells was measured using a NucleoCounter (ChemoMetec, Davis, CA, USA), and greater than 90% of the isolated cells were determined to be viable. Previous studies have demonstrated that the stromal vascular fraction of cells obtained with the Icellator system is highly enriched with CD31 − /CD34 + /CD45 − adipose derived MSCs [10]. …”
Section: Methodsmentioning
confidence: 99%
“…Recently, adult stem cells from bone marrow, umbilical cord blood, pancreatic duct, periosteum, and adipose tissue have shown a capacity to differentiate into insulin-producing cells [32][33][34][35][36][37][38][39][40][41][42][43] . Among the many tissue sources for adult stem cells, adipose tissue is particularly attractive based on its stem cell abundance and ease of tissue procurement through a minimally invasive and relatively inexpensive procedure [44][45][46][47][48] . Mesenchymal stem cells from bone marrow and adipose tissue share similar cell populations, along with cell characteristics [49][50][51] .…”
Section: Introductionmentioning
confidence: 99%